PERAN AGAMA DALAM MEMELIHARA KESEHATAN JIWA DAN SEBAGAI KONTROL SOSIAL MASYARAKAT - Azisi, Ali Mursyid (Al-Qalb : Jurnal Psikologi Islam, 2020)
Religion has such a central role in maintaining mental health and as a social control in the survival of people's lives. Religion also teaches to always do good to anyone and can reduce the occurrence of deviations. Based on the analysis and analysis of literature used in studying this article, it can also be concluded that religion is very important in life, especially religious people. Because, with the rules in religion, eventually directing every human being to a good life, orderly, far from deviations healthy physical and spiritual. In this article describes the role of religion in maintaining mental health and as a controller of the social life of the people who are the main pillars in survival in the community.